Implementation of Village Financial System Applications in Managing Village Fund: A Study in Papua- Indonesia - Merlina Hamadi, Melianus Bonsafia, Victor Pattiasina, Yohanes Cores Seral urin, Herman Umbu Kadubu (International Journal of Advanced Science and Technology, 2020)
The current study examines the implementation of the Village Financial System Application in Papua- Indonesia. It is a kind of empirical study conducted in Kampung District, Jayapura Regency, Papua- Indonesia. There were 71 respondents, while the sampling method used was saturated sample. Data collection was conducted through a direct survey. Hypothesis testing was examined empirically using multiple regression. The results showed that communication has affected the implementation of the village financial system application, while human resource has not affected the implementation of the village financial system application. Next, the disposition has affected the implementation of the village financial system application. Furthermore, the bureaucratic structure has had a negative effect, while the role of village facilitators has did not affect, and negative towards the implementation of the village financial system application. As a conclusion, it is stated that communication, human resources, disposition, bureaucratic structure, and village facilitators simultaneously influence the implementation of the village financial system application.